2014
DOI: 10.5901/mjss.2014.v5n26p37
|View full text |Cite
|
Sign up to set email alerts
|

Women Farmers’ Access and Use of Land For Agriculture in Selected Communities of Anambra State, Nigeria

Abstract: The study assessed women farmers '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…During key informant interview, participants reported, "Traditionally, women in this area do not own lands, houses and other assets". This corroborates with Enwelu, Morah, Dimelu and Ezeano (2014) that in Anambra State, women generally have limited access to farm land in the communities for subsistence farming. It further agrees with Enwelu et al, (2014) that women's right to the husband's land is secure as long as the marriage lasts and unmarried women are not allowed to inherit landed property in Anambra State even though they are actively involved in agricultural activities.…”
Section: Vulnerability Of Farmers To Cvc Impact and Gender Dynamics U...supporting
confidence: 85%
See 1 more Smart Citation
“…During key informant interview, participants reported, "Traditionally, women in this area do not own lands, houses and other assets". This corroborates with Enwelu, Morah, Dimelu and Ezeano (2014) that in Anambra State, women generally have limited access to farm land in the communities for subsistence farming. It further agrees with Enwelu et al, (2014) that women's right to the husband's land is secure as long as the marriage lasts and unmarried women are not allowed to inherit landed property in Anambra State even though they are actively involved in agricultural activities.…”
Section: Vulnerability Of Farmers To Cvc Impact and Gender Dynamics U...supporting
confidence: 85%
“…This corroborates with Enwelu, Morah, Dimelu and Ezeano (2014) that in Anambra State, women generally have limited access to farm land in the communities for subsistence farming. It further agrees with Enwelu et al, (2014) that women's right to the husband's land is secure as long as the marriage lasts and unmarried women are not allowed to inherit landed property in Anambra State even though they are actively involved in agricultural activities. This also agrees with Ekpo and Agu (2014) that women inherit land and property rights from neither their fathers nor husbands.…”
Section: Vulnerability Of Farmers To Cvc Impact and Gender Dynamics U...supporting
confidence: 85%
“…The result shows that less than half (49%) of women farmers had access to land as compared to the 65% of men who had access to land for rice production, which is significant at the 1% level. Enwelu et al [19] indicated that 98% of women had access to land through the involvement of a husband or a male relative in Nigeria. Again, compared to women, more men had significant access to labor than the women.…”
Section: Access and Control Of Resources By Men And Women Rice Farmer...mentioning
confidence: 99%
“…In addition, women's role within the social context often goes unrecognized [15]. In Ghana, the situation is not different; for instance, women farmers tend to have access to and control of production resources mainly through their husbands or male children, especially with regards to resources such as land and labor [3,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Women's access to land is still mediated via patriarchal systems where land is passed on to male descendants, despite the 1978 Land Use Act, through which all land was nationalized and authorized by the State Governor. Enwelu et al (2014) suggested that the conditions required for land tenure are beyond the financial capacity of many women.…”
Section: Factors For Success In Studied Casesmentioning
confidence: 99%